2021
DOI: 10.4018/jcad.20210701.oa2
|View full text |Cite
|
Sign up to set email alerts
|

China's Infrastructure Financing and the Role of Infrastructure in Awakening African Economies

Abstract: African economies, through Agenda 2063, recognize that developing infrastructure – transport, electricity, energy, water, and e-connectivity – will be critical for the region to assume a lasting place in the global economic system. As a result, this paper addresses the continent’s infrastructure gap and provides an important insight into the rapidly growing presence of China’s official infrastructure financing in Africa as well as the distinctive character of its involvement. In addition, the paper provides an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Along the same line, Effiom (2020) highlighted the positive influence of critical infrastructure development, such as transport and Information and Communications Technology (ICT), on Africa's long‐term economic growth and poverty reduction. Further empirical investigations by Ehizuelen (2021) using the generalized method‐of‐moments estimator revealed the positive effects of infrastructure quality on output and productivity in manufacturing and services in Africa. Likewise, Azolibe and Okonkwo (2020) found that telecommunications infrastructure quality significantly influences industrial productivity in sub‐Saharan African countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Along the same line, Effiom (2020) highlighted the positive influence of critical infrastructure development, such as transport and Information and Communications Technology (ICT), on Africa's long‐term economic growth and poverty reduction. Further empirical investigations by Ehizuelen (2021) using the generalized method‐of‐moments estimator revealed the positive effects of infrastructure quality on output and productivity in manufacturing and services in Africa. Likewise, Azolibe and Okonkwo (2020) found that telecommunications infrastructure quality significantly influences industrial productivity in sub‐Saharan African countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, infrastructure development is instrumental in facilitating industrial upgrading, improving structural efficiency, and fostering economic growth through inter-industry correlation effects. Besides, high-quality infrastructure positively impacts output and productivity in manufacturing and service sectors, leading to increased returns on private capital, as highlighted by Ehizuelen (2021). In developing nations, robust transportation networks play a critical role in attracting FDI, facilitating trade, reducing transaction costs, and promoting overall economic activity.…”
Section: Infrastructure Development Fdi and Economic Growthmentioning
confidence: 99%